A questionnaire-based survey in Spain provides relevant information to improve the control of ovine coccidiosis - Sánchez-Sánchez, Roberto; Gutiérrez, Jorge; Blasco-Castello, José Luis; Marcos-Santamaría, María; Cano-Alsua, Santiago; Elvira, Laura; Ferre, Ignacio; Ortega-Mora, Luis Miguel (Frontiers in Veterinary Science, 2023)
Ovine coccidiosis is a widespread intestinal parasitic disease caused by Eimeria spp. Lambs are infected by the ingestion of sporulated oocysts, experiencing diarrhea and low growth rates. Control should be based on measures to reduce infection pressure and stress on the animals as well as on appropriate diagnosis and strategic treatment. To obtain information on how control measures are implemented in the ovine sector in Spain, a questionnaire-based survey was completed in 2022 by 154 veterinarians and 173 farmers working in this sector. Coccidiosis was highlighted as a relevant disease by 34% of the respondents. The period of greatest risk seemed to differ between production systems, being mainly early after weaning (7-15 days after weaning) in meat flocks and feedlots and later (1-2 months after weaning) in dairy flocks. The absence of cleaning and disinfection measures was identified as a risk factor by 51% of the veterinarians, with 22% mentioning overcrowding of animals and 22% indicating that coccidiosis has more incidence in flocks with large number of animals. The use of laboratory diagnosis methods (fecal oocyst count) was unusual in 70% and 84% of the veterinarians and farmers, respectively. Regarding control, dairy flocks usually housed a larger number of animals under intensive conditions, and they implemented more frequently control measures for coccidiosis than meat flocks. Anticoccidial drugs were used in 79% of the flocks, and in 74-82% of them, they were applied based on clinical criteria. Comparing protocols for anticoccidial treatment among different production systems, in meat flocks, anticoccidial drugs were applied more frequently when clinical signs were observed, and coccidiostats were used for less than 28 days compared to dairy flocks. These results highlight the need for improvement in the use of anticoccidial treatments adjusted to the new regulatory framework in the EU, which in turn will rationalize the use of antimicrobial compounds and may help to mitigate the impact of coccidiosis in flocks.